Cerebral Drawings between Art and Science: On Gilles Deleuze's Philosophy of Concepts. (December 2015) - Schmidgen, Henning
In What Is Philosophy?, Gilles Deleuze and Félix Guattari distinguish the functions of philosophy, art and science. According to this distinction, the primary purpose of philosophy is to invent concepts, the purpose of art to bring forth percepts, or sensorial aggregates, and that of science to delineate functions . This article aims to show that these distinctions are not as clear-cut as they appear. Using Deleuze and Guattari's proposition that 'philosophy is the art of forming, inventing, and fabricating concepts' as a reference point, it suggests that the corresponding philosophical practice is intimately connected to art and science. Studying the conceptual drawings in Deleuze's texts, the article situates his philosophy in the French tradition of epistemology (Cavaillès, Bachelard and Canguilhem). As a result, the conceptual work of this philosophy can be seen as intensively responding to the creative problems posed by the dynamics of science in contemporary societies.